TIGA WUJUD PELAYANAN DALAM “PORTAL EMAS” SEBAGAI WUJUD E-GOVERMENT DENGAN PRINSIP ETIKA ADMINISTRASI NEGARA (ANALISIS PELAYANAN LISAN, TULISAN, DAN TINDAKAN DI KOTA PROBOLINGGO) - Supriyanto Supriyanto; Nurul Jannah Lailatul Fitria; Sahrul Hidayat (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
The government has responsibility for public sector services. The public services are intended to provide convenience and assistance to the public regarding what they need and to achieve an objective. Public services must understand and meet the community's needs regarding services, goods, and administration that need to be carried out properly. The forms of service can be verbal or written, or direct action. The governments, both local and central governments, need to improve the quality of service delivery. Therefore, the Probolinggo City Government had a strategy of providing quality public services. This public service innovation was called the "Portal Emas". The Portal Emas concept is a public service by implements three service forms in a digital application. The author researched the implementation of the Portal Emas as an application for public sector services. The objective was to find out whether the Portal Emas applied values to state administration ethical principles or not. The research was conducted using descriptive qualitative methods. The data was obtained through literature research as the primary source. This research collected scientific research related to public sector services and forms of service, then connected it with the state administration's ethical principles to determine that public service programs have well met the public services indicators. Therefore, public services could be known through the Portal Emas in Probolinggo City under the state administration's ethical principles by implementing three service forms in the Portal Emas application.